INVESTIGATION OF TEACHERS PERCEPTION ON THE USE OF VIRTUAL REALITY AS LEARNING MEDIA IN THE ELT SECONDARY SCHOOL CONTEXT - Ary Andriana Putra, Putu Wahyu; Santosa, M. H.; Saputra, I. N. P. H. (Lingua Scientia, 2020)
This research was aiming to investigate The English teachers related on their perception towards virtual reality (VR) as learning media in SMA N 4 Singaraja. The research used a mixed method with an explanatory sequential design. They were 2 English teachers that taught X grade students as the sample of this study. The data were obtained through two instruments from questionnaire and interview. Based on the validity and reliability checks, there were 6 dimensions use to develop the statement in questionnaire and 3 dimensions obtained from questionnaire to develop an interview guide. The result showed that the teachers' perception toward virtual reality in general was showed as very positive in general result. However, some challenges also appear during the research, part of them was obtained from the students that not quite well while operating the virtual reality device then, other challenges also come from the teacher while they were selecting the available material for the students as well as time-consuming during the preparation when virtual reality was implemented.Keywords : Perceptions, Teachers, Virtual Reality